Comparison of two tourniquet application times for regional intravenous limb perfusions with amikacin in sedated or anesthetized horses. (February 2016) - Aristizabal, F.A.; Nieto, J.E.; Guedes, A.G.; Dechant, J.E.; Yamout, S.; Morales, B.; Snyder, J.
Highlights: Regional limb perfusion is an effective technique to treat synovial and musculoskeletal infections in the distal limb. Two tourniquet times (20 and 30 min) were compared in two groups of horses, standing sedated and anesthetized. Intra-articular amikacin after 20 or 30 min RLP were equivalent despite the group. Amikacin concentrations were higher in the metacarpophalangeal joint in the standing sedated horses. In the radiocarpal joint, amikacin concentration was not different between groups. Abstract: Regional limb perfusion (RLP) in horses has proven to be a simple and effective technique for the treatment of synovial and musculoskeletal infections in the distal portion of the limbs. The ideal tourniquet time needed to achieve therapeutic synovial concentrations remains unknown. The pharmacokinetic effects of general anesthesia (GA) versus standing sedation (SS) RLP on synovial amikacin concentrations are not completely understood. This study investigated the pharmacokinetic effects of RLP under general anesthesia (GA) versus standing sedation (SS) on synovial amikacin concentration following 20 or 30 min tourniquet time. Using 1 g of amikacin RLP was performed in two groups of six horses (GA and SS). A pneumatic tourniquet was applied proximal to the carpus and maintained for 20 or 30 min. Two weeks later, the opposite treatment (20 or 30 min) was randomly performed in the opposite limb of horses in each group (GA and SS). Synovial fluid samples were collected from the metacarpophalangeal (MCP) and radiocarpal (RC) joints. Amikacin was quantified by a fluorescence polarization immunoassay. Regardless of the group, no significant difference in the synovial amikacin concentrations was noted between 20 and 30 min RLP. Mean synovial concentrations of amikacin in the standing sedated horses were significantly higher in the MCP joint at 30 min ( P  = 0.003) compared to horses under general anesthesia. No significant difference was noted for the RC joint.